Pemeriksaan C-Reactive Protein Sebagai Penanda Inflamasi dalam Upaya Awal Skrining Adanya Penyakit Menular Maupun Tidak Menular Pada Warga di Wilayah Binaan Desa Bone Kecamatan Nekamese Kabupaten Kupang - Ni Ketut Yuliana Sari; Agustina W. Djuma; Novian Agni Yudhaswara; Adrianus Ola Wuan; Agnes Rantesalu (Jurnal Pelayanan Masyarakat, 2024)
This community service activity was carried out in March 2024 in the fostered area of Bone Village, Nekamese District, Kupang Regency, located at the Gereja GMIT Tritunggal Pasneno, Bone. The activity carried out in the form of C-Reactive Protein (CRP) examination. CRP examination is a general inflammatory marker examination, so it can be a presumptive examination of inflammation in the body both caused by infectious and non-communicable diseases. The results of the examination of 43 samples showed reactive CRP as many as 2 samples (4.7%).